GYY4137, an H2S Slow-Releasing Donor, Prevents Nitrative Stress and α-Synuclein Nitration in an MPTP Mouse Model of Parkinson’s Disease - Hou, Xiaoou; Yuan, Yuqing; Sheng, Yulan; Yuan, Baoshi; Wang, Yali; Zheng, Jiyue; Liu, Chun-Feng; Zhang, Xiaohu; Hu, Li-Fang (Frontiers in Pharmacology, 2017)
The neuromodulator hydrogen sulfide (H2S) was shown to exert neuroprotection in different models of Parkinson’s disease (PD) via its anti-inflammatory and anti-apoptotic properties. In this study, we evaluated the effect of an H2S slow-releasing compound GYY4137 (GYY) on a mouse PD model induced by acute injection with 1-methyl-4-phenyl-1,2,3,6-tetrahydropyridine (MPTP). GYY was intraperitoneally (i.p.) injected once daily into male C57BL/6J mice three days before and two weeks after MPTP (14 mg/kg, four times at 2-hr intervals, i.p.) administration. Saline was given as a control. Behavioral tests (rotarod, balance beam, and grid walking) showed that 50 mg/kg GYY significantly ameliorated MPTP-caused motor impairments. At lower doses (12.5 and 25 mg/kg) GYY exhibited a less obvious effect. Consistent with this, immunohistochemistry and western blot analysis demonstrated that 50 mg/kg GYY attenuated the loss of tyrosine hydroxylase (TH) positive neurons in the substantia nigra and the decrease of TH expression in the striatum of MPTP-treated mice. Moreover, at this regimen GYY relieved the nitrative stress, as indicated by the decreases in nitric oxide (NO) generation and neuronal NO synthase (nNOS) upregulation elicited by MPTP in the striatum. The suppression of GYY on nNOS expression was verified in vitro, and the results further revealed that Akt activation may participate in the inhibition by GYY on nNOS upregulation. More important, GYY reduced the nitrated modification of α-synuclein, a PD-related protein, in MPTP-induced mice. Overall, our findings suggest that GYY attenuated dopaminergic neuron degeneration and reduced α-synuclein nitration in the midbrain, thus exerting neuroprotection in MPTP-induced mouse model of PD.